THE RELATIONSHIP OF FAMILY SUPPORT ON ACADEMIC ACHIEVEMENT OF MIDWIFERY STUDENTS AT THE MIDWIFERY ACADEMY - Setyowati, Ana; Maslikhah, Maslikhah (Politeknik Kesehatan Kementrian Kesehatan Gorontalo, 2025)
The factors that influence achievement in the world of education are multi-dimensional consequences that link several factors, including family, community, school, peers and the students themselves. Education is one means of forming and creating quality human resources. One important indicator of the results of education is achievement. Student learning achievement is influenced by internal and external factors of students. Family support is one factor that can influence student learning achievement.The research that will be carried out includes research that uses analytical observational studies with a cross-sectional research design. The sampling technique used puptpsive sampling, namely respondents who were willing to take part in the research. Sampling was carried out using a Google form link which was distributed via WhatsApp to all midwifery students at the Harapan Ibu Pekalongan Midwifery Academy. The type of analysis in this research uses the Kendall Tau test analysis. The results of the research obtained a p value of 0.021 which shows that there is a significant relationship between family support and the level of student learning achievement as evidenced by the cumulative achievement index (GPA) with a correlation coefficient value of 0.362 showing that there is a sufficient correlation or relationship between family support and student learning achievement